A Comparative Study of Amide Proton Transfer Weighted Imaging and Intravoxel Incoherent Motion MRI Techniques Versus (18) F‐FDG PET to Distinguish Solitary Pulmonary Lesions and Their Subtypes. Issue 5 (15th April 2022) - Fang, Ting; Meng, Nan; Feng, Pengyang; Huang, Zhun; Li, Ziqiang; Fu, Fangfang; Yuan, Jianmin; Yang, Yang; Liu, Hui; Roberts, Neil; Wang, Meiyun
Abstract : (A–H) A 64‐year‐old male patient, with adenocarcinoma (AC) in the left lung, (A) is D pseudocolored map with D = 1.08 × 10 −3 mm 2 /second, (B) is F pseudocolored map with F = 22.5%, (C) is D* pseudocolored map with D* = 18.36 × 10 −5 mm 2 /second, (D) is T2W image with fat saturation pre‐pulse, (E) is hematoxylin and eosin (H&E) staining image which confirms this SPLs to be AC, (F ) is the fusion image of the SUV map and the attenuation correction map with SUVmax = 14.29, (G) is the B0 map, (H) is the mtrasym map with mtrasym (3.5 ppm) (%) = 7.3%. D = diffusion coefficient; F = perfusion fraction; D* = pseudo diffusion coefficient; SPLs = solitary pulmonary lesions; AC = adenocarcinoma; SUVmax = maximum value of standard uptake value; MTRAsym = magnetization transfer ratio asymmetry. by Ting Fang et al. (1376–1390)